2017
DOI: 10.5186/aasfm.2017.4253
|View full text |Cite
|
Sign up to set email alerts
|

Rigidity theorems for minimal submanifolds in a hyperbolic space

Abstract: Abstract. Let M be a complete immersed minimal hypersurface in a hyperbolic space. In this paper we establish conditions on the first eigenvalue of the stability and super stability operators and the L d norm of the length of the second fundamental form of M to imply that M is totally geodesic. Similar results for minimal submanifolds in a hyperbolic space are also proven.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Simon's work has been of great interest to differential geometers, and in the last decade several interesting gap theorems for submanifolds have been successfully obtained. We refer the reader to [1], [2], [3], [4], [5], [7], [9], [10], [11], [13], [14], and the references therein.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Simon's work has been of great interest to differential geometers, and in the last decade several interesting gap theorems for submanifolds have been successfully obtained. We refer the reader to [1], [2], [3], [4], [5], [7], [9], [10], [11], [13], [14], and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…In this direction, the first author and Wang studied in [3] the stability operator for complete minimal submanifolds M n in H n+m . They showed that if the condition (1.2) is satisfied and the first eigenvalue of the super stability operator is greater than a certain constant, then a Simon's type theorem holds if 2 ≤ n ≤ 5, and for all n = 3 if m = 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation